The Ethnic Mobility Trap and Stratification Theory. (6th August 2014) - Wiley, Norbert F.
Abstract : A mobility trap is a structural condition in which the means for moving up within a stratum are contrary to those for moving to the next higher stratum. The underlying metaphor is that of climbing a tree, rather than a "social ladder, " with various possibilities of non-vertical and dead-end forms of ascent. Within this framework several theoretical issues are reformulated: (a) the chances for mobility at different levels within a stratum, (b) the meaning and utility of "anticipatory socialization" in mobility analysis, (c) the conditions under which the members of a class will misperceive the norms of other classes, (d) the conditions under which mobility will bring stress, (e) the nature and effects of status inconsistency, and (f) the restraints against political radicalism in the United States.